Eternal Love: An Exploration Of The Concept Of Qur'anic Marriage According To Ash-Shā'rawī In Tafseer Khawātir Ash-Shā'rāwī (Thematic Approach) - Anggara, Deki Ridho Adi; Septrianto, Wahyu; Mustikasari, Intan Pratiwi; Mutmainah, Amaliah Mukmilatun; Nor, Azhar (ZAD Al-Mufassirin, 2024)
Conflict in the household is one of the causes of divorce that occurs today. This shows that some people do not fully understand the concept of marriage. In fact, marriage is a covenant so strong that it becomes one of the divine commitments called mītsāqan ghalīẓa (marriage bond). This study aims to examine how the concept of marriage according to Ash-Sha'rāwī in his tafsir Khawatir Ash-Sha'rāwī. This research method is descriptive and analytical through literature study with a thematic approach. The results showed that the concept of marriage according to Sha'rāwī is an agreement taken by two parties, namely the marriage contract. This is not an ordinary agreement, but a strong agreement, which requires the husband to take responsibility and get along well. Therefore, the husband and wife or the bride and groom who are about to marry must know and understand the concept of marriage very well, which includes the nature of mīṡāqan ghalīẓa, the rights and duties of husband and wife, and how to resolve family conflicts.